Germline mutations in patients with oral mucosal leukoplakia and squamous cell carcinoma: a prospective observational study - N. A. Karpuk; S. P. Rubnikovich; O. Ch. Mazur; I. V. Zhyltsov; I. Yu. Karpuk; A. P. Mikhalenka (Кубанский научный медицинский вестник, 2023)
Background. The number of studies devoted to the molecular genetics of oral mucosal leukoplakia and squamous cell carcinoma is small, while the obtained results are usually preliminary in nature. We can assume the existence of region-specific pathogenic genetic variants involved in the development of oral mucosal leukoplakia and squamous cell carcinoma. With the knowledge of such variants, it would become possible to develop PCR (polymerase chain reaction) and NGS (next-generation sequencing) test systems for the detection of clinically significant germline mutations.Objectives — to identify pathogenic germline genetic variants in patients with oral mucosal leukoplakia accompanied by grade 1 epithelial dysplasia, as well as oral mucosal squamous cell carcinoma, using new-generation sequencing.Methods. Study design: prospective, observational, cross-sectional, without a control group. The sample included patients (48 persons) of either sex (18 years of age or older) with the following proven and morphologically confirmed diagnoses: oral mucosal leukoplakia accompanied by grade 1 squamous intraepithelial neoplasia of epithelium (24 people) and oral mucosal squamous cell carcinoma (24 people), who sought medical care at the Vitebsk Regional Clinical Dental Center and Vitebsk Regional Clinical Oncological Center in 2019–2020. The identified pathogenic and presumably pathogenic genetic variants involved in the development of these diseases were quantitatively assessed. The study was conducted at the Shareable Core Facilities GENOME of the Institute of Genetics and Cytology of the National Academy of Sciences of Belarus. In order to isolate deoxyribonucleic acid (DNA) from blood samples, a QIAamp DNA FFPE Tissue Kit (Qiagen, Germany) was used. The preparation of DNA libraries and sequencing were carried out by means of an Illumina NextSeq 550 sequencing system (Illumina, Inc., USA) using an Illumina Nextera DNA Exome kit (USA). Bioinformatic analysis was conducted using Illumina BaseSpace specialized software (USA) and Galaxy Project (Galaxy Community, an international non-profit project) in accordance with current guidelines. The obtained data were statistically processed employing specialized software packages Statistica 12 (StatSoft, Inc., USA) and MedCalc 18.9.1 (MedCalc Software, Ltd, Belgium).Results. Next-generation whole-exome sequencing of deoxyribonucleic acid samples isolated from the blood of patients with oral mucosal leukoplakia and squamous cell carcinoma has been conducted in the Republic of Belarus for the first time. The total number of unique germline genetic variants in the exome of both groups of patients was shown to be very high, yet most of them were not pathogenic. In the examined patients, the majority of germline mutations were found to be localized only in 19 exome genes: MAP2K3, DNAH5, HSPG2, OBSCN, SYNE1, HLA-DRB1, HLA-DQA1, HLA-DQB1, HLA-A, HLA-B, PKD1L2, TTN, AHNAK2, PDE4DIP, MUC3A, MUC4, MUC12, MUC16, and MUC17. In both clinical groups, the greatest number of genetic variants (> 40% of the total number) was detected in MUC3A, MUC4, MUC12, and MUC16, responsible for the synthesis of the glycoprotein mucin family.Conclusion. Oral mucosal leukoplakia and squamous cell carcinoma can arise from the pathogenic variants of MUC3A, MUC4, MUC12, and MUC16.